Exploration of Novel Motifs Derived from Mouse cDNA Sequences - Kawaji, Hideya (Cold Spring Harbor Laboratory Press, 2002)
We performed a systematic maximum density subgraph (MDS) detection of conserved sequence regions to discover new, biologically relevant motifs from a set of 21,050 conceptually translated mouse cDNA (FANTOM1) sequences. A total of 3202 candidate sequences, which shared similar regions over >20 amino acid residues, were screened against known conserved regions listed in Pfam, ProDom, and InterPro. The filtering procedure resulted in 139 FANTOM1 sequences belonging to 49 new motif candidates. Using annotations and multiple sequence alignment information, we removed by visual inspection 42 candidates whose members were found to be false positives because of sequence redundancy, alternative splicing, low complexity, transcribed retroviral repeat elements contained in the region of the predicted open reading frame, and reports in the literature. The remaining seven motifs have been expanded by hidden Markov model (HMM) profile searches of SWISS-PROT/TrEMBL from 28 FANTOM1 sequences to 164 members and analyzed in detail on sequence and structure level to elucidate the possible functions of motifs and members. The novel and conserved motif MDS00105 is specific for the mammalian inhibitor of growth (ING) family. Three submotifs MDS00105.1–3 are specific for ING1/ING1L, ING1-homolog, and ING3 subfamilies. The motif MDS00105 together with a PHD finger domain constitutes a module for ING proteins. Structural motif MDS00113 represents a leucine zipper-like motif. Conserved motif MDS00145 is a novel 1-acyl-SN-glycerol-3-phosphate acyltransferase (AGPAT) submotif containing a transmembrane domain that distinguishes AGPAT3 and AGPAT4 from all other acyltransferase domain-containing proteins. Functional motif MDS00148 overlaps with the kazal-type serine protease inhibitor domain but has been detected only in an extracellular loop region of solute carrier 21 (SLC21) (organic anion transporters) family members, which may regulate the specificity of anion uptake. Our motif discovery not only aided in the functional characterization of new mouse orthologs for potential drug targets but also allowed us to predict that at least 16 other new motifs are waiting to be discovered from the current SWISS-PROT/TrEMBL database.